Homojunction Cu2O Solar Cells Fabricated with Various Impurity-Doped Epitaxially Grown n-Type Cu2O Thin Film by Electrochemical Deposition. (25th October 2017) - Miyata, Toshihiro; Yamazaki, Jouji; Watanabe, Kyosuke; Tokunaga, Hiroki; Minami, Tadatsugu
Abstract : This paper describes the photovoltaic properties of homojunction Cu2 O solar cells fabricated with various impurity-doped epitaxially grown n-type or i-type Cu2 O thin films by an electrochemical deposition (ECD) method. Significantly enhanced open circuit voltage (VOC ) and conversion efficiency (η) were achieved in AZO/Cu2 O:Cl/p-Cu2 O:Na and/or AZO/Cu2 O:Mn/p-Cu2 O:Na homojunction solar cells fabricated by Cu2 O:Cl and/or Cu2 O:Mn thin films as the n- or i-type layer using ECD; these values were higher than those obtained in AZO/n-ZnO/p-Cu2 O heterojunction solar cells. The obtained enhanced Voc and η suggest that the Cu2 O:Cl and/or the Cu2 O:Mn thin film layers act as an n- or i-type appropriate active layer. The highest Voc, short-circuit current density (JSC ), and the conversion efficiencies for AZO/n-type Zn-Ge-O thin film/Cu2 O:Mn/Cu2 O:Na homojunction solar cells were 0.84 V, 10.1 mA/cm 2, and 4.74%, respectively.